2021
DOI: 10.5194/hess-25-257-2021
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitous increases in flood magnitude in the Columbia River basin under climate change

Abstract: Abstract. The USA and Canada have entered negotiations to modernize the Columbia River Treaty, signed in 1961. Key priorities are balancing flood risk and hydropower production, and improving aquatic ecosystem function while incorporating projected effects of climate change. In support of the US effort, Chegwidden et al. (2017) developed a large-ensemble dataset of past and future daily streamflows at 396 sites throughout the Columbia River basin (CRB) and selected other watersheds in western Washington and Or… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 35 publications
(51 reference statements)
2
18
0
Order By: Relevance
“…occur; however, as the susceptible range of snow rises to higher elevations under warming, the number of events could increase by an additional day or two in the future (Mussleman et al 2018). Queen et al (2021) found that warming and a shift to more rain-dominated precipitation will likely extend the flood season on the Upper Snake River around Jackson WY (presently from mid-May to mid June), to earlier in the year and increase the magnitude of large floods (10-year and 100-year recurrence interval).…”
Section: Runoff Considered By Elevationmentioning
confidence: 99%
“…occur; however, as the susceptible range of snow rises to higher elevations under warming, the number of events could increase by an additional day or two in the future (Mussleman et al 2018). Queen et al (2021) found that warming and a shift to more rain-dominated precipitation will likely extend the flood season on the Upper Snake River around Jackson WY (presently from mid-May to mid June), to earlier in the year and increase the magnitude of large floods (10-year and 100-year recurrence interval).…”
Section: Runoff Considered By Elevationmentioning
confidence: 99%
“…Although Queen et al. (2021) do not show detailed results from RCP4.5, they state that that “to first order the changes in flood magnitude in RCP4.5 were ∼2/3 those in RCP8.5.” The Columbia River, along much of its mainstem, is an important exception to their generalization and the cause for the nonmonotonic response to increased anthropogenic forcing may lie in changes in mainstem‐tributary synchrony, which we discuss in Section 3.4.…”
Section: Resultsmentioning
confidence: 99%
“…AMFs with relatively low synchrony also occur more frequently in the future scenarios, extending the lower tail of the distribution of α (e.g., Figures 3b and 3c). One explanation for the decreased synchrony is the region‐wide shift toward an earlier freshet occurring at different rates among tributaries (Queen et al., 2021). Because the snowpack in the colder headwaters, such as the upper Columbia headwaters in the Canadian Rockies, is less impacted by the projected warming than the snowpack in warmer headwaters that tend to feed the downstream tributaries (e.g., Chegwidden et al., 2019), the relative timing of the freshet can be expected to diverge across many tributaries to the Columbia.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations